2005
DOI: 10.4319/lo.2005.50.5.1362
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of temperature and nutrient limitation on the response of alpine phytoplankton growth to ultraviolet radiation

Abstract: We performed bag-enclosure experiments for 7 d in a lake in the Beartooth Mountains (in Montana and Wyoming) using natural phytoplankton assemblages. Ultraviolet radiation (UVR) (exposed or blocked), temperature (6ЊC and 14ЊC), and nutrients (nitrogen, phosphorus, and nitrogen plus phosphorus) were manipulated in a factorial design to determine how these factors interact to affect phytoplankton growth. Four major phytoplankton taxa (two diatoms, one chrysophyte, and one dinoflagellate) were found in the water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 28 publications
5
70
0
Order By: Relevance
“…4d-f). This finding is consistent with the ameliorating effect of moderate temperature increase on the net biological UVR effect reported on photosynthesis and growth of different phytoplankton species [25][26][27][28] and in the relatively higher germination capacity of UVR-exposed Alaria marginata zoospores at 15 • C compared to 10 • C. 32 Non-photochemical dissipation of excess light energy is a shortterm response, first-line defence and one of the most efficient protective mechanisms against photostress. 68, 69 Consequently, during 8 and 48 h measurements, we observed no consistent relationship between combined light and thermal stress and changes in light energy dissipation via a non-photochemical pathway; a similar response was observed in high-and low-light acclimated dinoflagellates subjected to thermal stress.…”
Section: Discussionsupporting
confidence: 86%
“…4d-f). This finding is consistent with the ameliorating effect of moderate temperature increase on the net biological UVR effect reported on photosynthesis and growth of different phytoplankton species [25][26][27][28] and in the relatively higher germination capacity of UVR-exposed Alaria marginata zoospores at 15 • C compared to 10 • C. 32 Non-photochemical dissipation of excess light energy is a shortterm response, first-line defence and one of the most efficient protective mechanisms against photostress. 68, 69 Consequently, during 8 and 48 h measurements, we observed no consistent relationship between combined light and thermal stress and changes in light energy dissipation via a non-photochemical pathway; a similar response was observed in high-and low-light acclimated dinoflagellates subjected to thermal stress.…”
Section: Discussionsupporting
confidence: 86%
“…UVR inhibition is likely greater in cold waters, since enzymatically controlled repair mechanisms in cells are temperature-dependent in contrast to the photochemical damage by UVR (Milot-Roy & Vincent 1994, Doyle et al 2005. In the present study, primary production was substantially reduced in the presence of UVR in GKS (56% reduction of P tot ), followed by NYA (30% reduction of P tot ; Fig.…”
Section: Uvr Effects and Ecosystem Implicationssupporting
confidence: 54%
“…For example, it has been found that the effect of UVBR may be temperature dependent because temperature enhances photo-enzymatic repair (Williamson et al 2002;MacFadyen et al 2004). Another study (Doyle et al 2005) has shown that the effect of UVBR on phytoplankton growth is not only temperature dependent but also nutrient dependent. Therefore, studying the response of the entire plankton food web to multiple stressors linked to global change with an emphasis on direct (i.e., physiological) and indirect (i.e., positive or negative feedbacks) effects of complex interactions is essential to evaluating how global change will modify the structure and function of aquatic systems.…”
mentioning
confidence: 99%